2016
DOI: 10.1371/journal.pmed.1001964
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, Morbidity, and Developmental Outcomes in Infants Born to Women Who Received Either Mefloquine or Sulfadoxine-Pyrimethamine as Intermittent Preventive Treatment of Malaria in Pregnancy: A Cohort Study

Abstract: BackgroundLittle is known about the effects of intermittent preventive treatment of malaria in pregnancy (IPTp) on the health of sub-Saharan African infants. We have evaluated the safety of IPTp with mefloquine (MQ) compared to sulfadoxine-pyrimethamine (SP) for important infant health and developmental outcomes.Methods and FindingsIn the context of a multicenter randomized controlled trial evaluating the safety and efficacy of IPTp with MQ compared to SP in pregnancy carried out in four sub-Saharan countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…In the present study, the incidence of a positive blood film for malaria parasites at delivery was lower among participants who received mefloquine than among those who received sulphadoxine–pyrimethamine, but this difference was not significant. This finding was similar to that of a multicenter study conducted by Ruperez et al., and comparable with the findings of González et al . The incidence of placenta parasitization was lower in the mefloquine group than in the sulphadoxine–pyrimethamine group, although again the difference was not significant.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the incidence of a positive blood film for malaria parasites at delivery was lower among participants who received mefloquine than among those who received sulphadoxine–pyrimethamine, but this difference was not significant. This finding was similar to that of a multicenter study conducted by Ruperez et al., and comparable with the findings of González et al . The incidence of placenta parasitization was lower in the mefloquine group than in the sulphadoxine–pyrimethamine group, although again the difference was not significant.…”
Section: Discussionsupporting
confidence: 92%
“…However, as the sample size was just 248 subjects, the safety findings from this study need to be interpreted with caution. The incidence of vomiting was significantly higher in women who received AS+MQ than in those who received AS+SP which confirms the finding of a high incidence of vomiting when MQ was used for intermittent preventive treatment in pregnant women [ 21 ]. The PREGACT study also reported a high frequency of vomiting in AS+MQ group [ 18 ].…”
Section: Discussionsupporting
confidence: 76%
“…However, the child's age at first malaria episode was assessed only through interview of the mother, and malaria blood smears were only performed at 1 week, 2 months and 9 months of age . Three more recent trials in Africa comparing IPTp‐SP with either, long‐lasting insecticide‐treated bed nets, mefloquine or intermittent screening and treatment with artemether‐lumefantrine also found that the incidence of malaria from birth to 12 months of age was similar in intervention and control groups of children. However, in each of these settings, the experimental group was not shown to significantly reduce the burden of PM in comparison with control …”
Section: Can Prevention or Treatment Of Malaria In Pregnancy Alter Thmentioning
confidence: 99%